Analysis of The Use of Problem-Based Learning Model in Improving Learning Outcomes of Hindu Religious Education in Grade V Students of UPT SD Negeri 6 Arawa Sidrap - Langka, Rosmidah; Suarnaya, I Putu (Jayapangus Press, 2024)
The learning process does not teach students to work together in groups, resulting in less active learning. Students also lack the critical thinking skills required to solve problems. This issue arises due to teachers' lack of knowledge and the absence of innovative learning models. Consequently, it leads to low student learning outcomes, necessitating research to examine this matter. The objective of this study is to analyze the implementation of a problem-based learning model in improving the learning outcomes of Hindu religious education in grade V students of UPT SD Negeri 6 Arawa, Sidrap Regency. The research approach employed is qualitative research with the type of library research. Data sources include books, scientific journals, magazines, newspapers, and other relevant information. The informants were selected based on their relevance to the topic under study. Research instruments comprised books, scientific journals, and other relevant documents. The data collection technique employed was documentation study, while qualitative content analysis was used for data analysis. The findings indicate that the problem-based learning model is an appropriate choice for teachers who wish to develop students' analytical abilities, enable them to apply existing knowledge in new situations, and encourage independent and responsible problem-solving skills. This model enhances students' critical, analytical, systematic, and logical thinking abilities, enabling them to find alternative solutions to problems through empirical data exploration, ultimately fostering a scientific attitude. In conclusion, the use of problem-based learning models can improve learning outcomes in Hindu religious education in grade V students of UPT SD Negeri 6 Arawa Sidrap.